Pericardial effusion following percutaneous left atrial appendage closure using the LAmbre device - Yu, Yibo; Chu, Huimin; Wang, Binhao; He, Bin; Fu, Guohua (Frontiers in Cardiovascular Medicine, 2023)
Background Pericardial effusion (PE) is an uncommon but serious complication that occurs following percutaneous left atrial appendage closure (LAAC). There are few data regarding PE following implantation of the LAmbre device for LAAC. Methods Patients with nonvalvular atrial fibrillation (AF) undergoing percutaneous LAAC using the LAmbre device at the Arrhythmia Center of Ningbo First Hospital from October 2017 to March 2021 were retrospectively reviewed (n=133). PE was defined as acute if diagnosed ≤ 7 days post LAAC (n=3, 2.3%) or delayed if diagnosed > 7 days post LAAC (n=3, 2.3%). The clinical characteristics and procedural data were compared between patients with PE (PE group, n=6) and without PE (non-PE group, n=127). The predictors of PE were analyzed by logistic regression. Results All patients with PE recovered following treatment by pericardiocentesis. Patients with PE were found to have a higher incidence of congestive heart failure (50.0% vs. 13.4%, P=0.044) and had larger measured LAA orifice diameters (33.5±6.0 mm vs. 28.3±5.2 mm, P=0.018) and landing zone diameters (27.8±4.8 mm vs. 23.9±4.8 mm, P=0.054) compared with those without PE. The diameters of the device umbrellas (31.7±5.6 mm vs. 26.9±5.0 mm, P=0.026) and covers (36.3±4.6 mm vs. 33.4±4.0 mm, P=0.075) implanted were larger in the PE group compared to the non-PE group. Univariate logistic regression revealed that congestive heart failure (OR=6.47, 95% CI 1.21-34.71, P=0.029) and LAA maximal orifice diameter (OR=1.22, 95% CI 1.02-1.45, P=0.027) were both associated with PE following LAmbre device implantation. Conclusions In this single-center experience, both acute and delayed PE were uncommon in patients with AF following LAmbre device implantation. Congestive heart failure and a larger LAA orifice were identified as predictors for the occurrence of PE.